Guide to Owning a Hamster : Accommodations, feeding, breeding, exhibition, health care - Barrie, Anmarie (Neptune City, N.J. : T.F.H., 1996)
Guide to Owning a Hamster offers informative, easy-to-read text accompanied by illustrations.
Includes index.
Keywords: Hamsters as pets; Pets